Aspects of Criminal Policy and Law Enforcement Science - Blaskó, Béla; Pallagi, Anikó (Magyar Rendészet, 2020)
The authors examine the connection between law enforcement activities, law enforcement science and the scientific system of criminal policy, their mutual presumption and interaction. The law enforcement activities serve to uphold law, order and public security against unlawful human behaviours. The criminalisation of certain types of behaviour is a quasi fundamental resultant of law enforcement activity, which may provide criminal policy with a guideline by realising activities dangerous to society, or antisocial during its operation. In addition to the above, however, the relationship is multi-directional as the state receives information on the current status of crimes in the course of the completion of law enforcement tasks, and the quality of the completion of law enforcement tasks fundamentally influences the course of crimes.